2006
DOI: 10.1002/jmri.20577
|View full text |Cite
|
Sign up to set email alerts
|

Combining EEG and fMRI: A multimodal tool for epilepsy research

Abstract: Patients with epilepsy often present in their electroencephalogram (EEG) short electrical potentials (spikes or spikewave bursts) that are not accompanied by clinical manifestations but are of important diagnostic significance. They result from a population of abnormally hyperactive and hypersynchronous neurons. It is not easy to determine the location of the cerebral generators and the other brain regions that may be involved as a result of this abnormal activity. The possibility to combine EEG recording with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
175
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 252 publications
(187 citation statements)
references
References 127 publications
9
175
1
2
Order By: Relevance
“…These limitations could potentially be mitigated if icEEG recording were used in combination with functional MRI (fMRI). Indeed, despite its own limitations scalp EEG has previously been successfully combined with fMRI in study patients with epilepsy, providing unique new information on the haemodynamic correlates of paroxysmal discharges in a good proportion of cases studied to date [4][5][6][7][8]. Importantly, these include brain areas thought to be primarily responsible for the generation of interictal and ictal epileptic discharges visible on scalp EEG recordings [5,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations could potentially be mitigated if icEEG recording were used in combination with functional MRI (fMRI). Indeed, despite its own limitations scalp EEG has previously been successfully combined with fMRI in study patients with epilepsy, providing unique new information on the haemodynamic correlates of paroxysmal discharges in a good proportion of cases studied to date [4][5][6][7][8]. Importantly, these include brain areas thought to be primarily responsible for the generation of interictal and ictal epileptic discharges visible on scalp EEG recordings [5,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, despite its own limitations scalp EEG has previously been successfully combined with fMRI in study patients with epilepsy, providing unique new information on the haemodynamic correlates of paroxysmal discharges in a good proportion of cases studied to date [4][5][6][7][8]. Importantly, these include brain areas thought to be primarily responsible for the generation of interictal and ictal epileptic discharges visible on scalp EEG recordings [5,7,9,10]. However, EEG-fMRI studies in epilepsy have raised a number of important questions, for example; 1) is normal neurovascular coupling maintained, as in cognitive fMRI experiments [12][13][14][15][16]?…”
Section: Introductionmentioning
confidence: 99%
“…With simultaneous EEG recording, BOLD correlates of EEG events can also be studied, such as epileptiform events (Gotman et al, 2006) or evoked potential (Horovitz et al, 2002;Bénar et al, 2007). In the same way, EEG-fMRI can be used to analyze the BOLD effect of each type of EEG oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Using the interictal spikes detected on scalp EEG as events, we can identify hemodynamic changes in the whole brain. Several studies demonstrated that this method provides valuable information about the generators of interictal spikes (Gotman et al, 2006), i.e. the irritative zone (Rosenow and Lueders, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of these two variables on the shape of the HRF is unknown. However, there is evidence that studies with larger numbers of spikes are more likely to result in BOLD responses than those with small numbers (Gotman et al, 2006). On the other hand, the general linear model (GLM) used for statistical analyses in EEG-fMRI may fail or be inaccurate with high event numbers, as this model postulates that the response of two closely spaced events will sum linearly (Friston et al, 1998).…”
Section: Introductionmentioning
confidence: 99%